2011
DOI: 10.2215/cjn.11351210
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Hypertension and its Association with Endothelial Cell Dysfunction

Abstract: SummaryBackground and objectives Intradialytic hypertension is associated with adverse outcomes, yet the mechanism is uncertain. Patients with intradialytic hypertension exhibit imbalances in endothelial-derived vasoregulators nitric oxide and endothelin-1, indirectly suggesting endothelial cell dysfunction. We hypothesized that intradialytic hypertension is associated in vivo with endothelial cell dysfunction, a novel predictor of adverse cardiovascular outcomes. Design, settings, participants, & measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…23 In addition, Inrig et al 24 showed that the number of peripheral endothelial progenitor cells in 25 hemodialysis patients with intradialytic hypertension is by 50% higher than in 25 ageand sex-matched controls with normal intradialytic BP profile, an alteration accompanied by reduced endothelium-dependent vasodilatation. Thus, patients with intradialytic hypertension display severely impaired endothelial repair capacity and diminished endothelial response to shear stress.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…23 In addition, Inrig et al 24 showed that the number of peripheral endothelial progenitor cells in 25 hemodialysis patients with intradialytic hypertension is by 50% higher than in 25 ageand sex-matched controls with normal intradialytic BP profile, an alteration accompanied by reduced endothelium-dependent vasodilatation. Thus, patients with intradialytic hypertension display severely impaired endothelial repair capacity and diminished endothelial response to shear stress.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Brachial Artery Vasodilation. Testing of brachial artery FMD and nitroglycerin-mediated vasodilation was per standard guidelines and per our previously published protocol (5,19). Briefly, the brachial artery diameter was measured at baseline and after 5 minutes of brachial artery occlusion.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Recent investigations have identified imbalances in EC-derived mediators of vascular function, including intradialytic increases in plasma endothelin-1 (ET-1) relative to nitric oxide among those with intradialytic hypertension (6,7). We have identified in vivo impairments in EC function among participants with intradialytic hypertension compared with controls, as measured by lower endothelial progenitor cells (EPCs) and impaired flow-mediated vasodilation (FMD) (5). Considering that EC dysfunction seems to be one of the primary mechanisms responsible for intradialytic hypertension and is independently predictive of adverse cardiovascular outcomes (10)(11)(12)(13), we propose that targeting EC dysfunction may represent a novel therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…These were measured prior to dialysis, so that they also were not influenced by the haemodialysis procedure. It is of note that in the Inrig et al study [38], the change of plasma ET-1 concentration from pre-to post-haemodialysis was not different between the intradialytic hypertension patients and haemodialysis controls. So, while endothelial cell dysfunction appears to be more pronounced in intradialytic hypertension patients, the most recent research has focused on specific mechanisms, by which the endothelial cells influence intradialytic blood pressure [40].…”
Section: Blood Pressure Variability Among Haemodialysis Patientsmentioning
confidence: 63%
“…Based on the evidence that vasoconstriction may be a predominant mechanism for intradialytic hypertension and that ET-1 has been implicated as a causative mediator for this, further investigation has to be directed toward the overall role of endothelial cell dysfunction in intradialytic hypertension. It was found that patients with intradialytic hypertension had lower flow-mediated vasodilation [38]. This assessment of endothelial cell function occurred on a non-haemodialysis day so it was not influenced by the haemodialysis procedure.…”
Section: Blood Pressure Variability Among Haemodialysis Patientsmentioning
confidence: 83%